2017
DOI: 10.1038/nsmb.3457
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an inactivated mutant mammalian voltage-gated K+ channel

Abstract: C-type inactivation underlies important roles played by voltage-gated K+ (Kv) channels. Functional studies have provided strong evidence that a common underlying cause of this type of inactivation is an alteration near the extracellular end of the channel's ion selectivity filter. Unlike N-type inactivation, which is known to reflect occlusion of the channel's intracellular end, the structural mechanism of C-type inactivation remains controversial and may have many detailed variations. Here, we report that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 49 publications
5
69
0
Order By: Relevance
“…Indeed, this slow inactivation is thought to involve the collapse of the pore P-loop, which shapes the selectivity filter ( Fig. 12B; Cuello et al 2010;Payandeh et al 2012;Zhang et al 2012;Li et al 2017;Pau et al 2017), at a remote distance from the activation gate facing the intracellular end of the channel. Such a model has been proposed initially for the prototypical voltage-gated Shaker potassium channel and the prokaryotic KcsA channel, although it has also been shown to be responsible for the run-down of distantly related TRPM2 channels (Toth & Csanady, 2012).…”
Section: Comparison With Other Ion Channels: High Prevalence Of a Twomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this slow inactivation is thought to involve the collapse of the pore P-loop, which shapes the selectivity filter ( Fig. 12B; Cuello et al 2010;Payandeh et al 2012;Zhang et al 2012;Li et al 2017;Pau et al 2017), at a remote distance from the activation gate facing the intracellular end of the channel. Such a model has been proposed initially for the prototypical voltage-gated Shaker potassium channel and the prokaryotic KcsA channel, although it has also been shown to be responsible for the run-down of distantly related TRPM2 channels (Toth & Csanady, 2012).…”
Section: Comparison With Other Ion Channels: High Prevalence Of a Twomentioning
confidence: 99%
“…; Pau et al . ), at a remote distance from the activation gate facing the intracellular end of the channel. Such a model has been proposed initially for the prototypical voltage‐gated Shaker potassium channel and the prokaryotic KcsA channel, although it has also been shown to be responsible for the run‐down of distantly related TRPM2 channels (Toth & Csanady, ).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation of C‐type inactivation involves either SF dilatation at the K + binding site Site 1 (Hoshi & Armstrong, ), or a constriction of the SF at Site 4 (Pau et al . ), leading to its partial dehydration and corresponding loss of an efficient knock‐on mechanism. A recent combined MD and experimental study of the Shaker K V channel demonstrated that the SF widening associated with C‐type inactivation is a result of the pore domain being pulled outward towards the VSD (Conti et al .…”
Section: Mechanisms Of Ion Channel Gatingmentioning
confidence: 99%
“…An alternative explanation of C-type inactivation involves either SF dilatation at the K + binding site Site 1 (Hoshi & Armstrong, 2013), or a constriction of the SF at Site 4 (Pau et al 2017), leading to its partial dehydration and corresponding loss of an efficient knock-on mechanism.…”
Section: N-and C-type Inactivationmentioning
confidence: 99%
“…All prior K2P structure selectivity filters ( Fig. S5a-b) (denoted as the 'native state') as well as selectivity filters from other potassium channels thought to capture either conducting states 21,26 or, surprisingly, inactivated states 21,27 , map to the center of this group ( Fig. S5c).…”
mentioning
confidence: 99%